1997
DOI: 10.1111/j.1432-1033.1997.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

1α,25‐Dihydroxyvitamin D3 and a Variety of its Natural Metabolites Transcriptionally Repress Nuclear‐Factor‐κB‐Mediated Interleukin‐8 Gene Expression

Abstract: Regulation of interleukin-8 (IL-8) gene transcription occurs mainly through the sequences -94 to -71 of the 5'-flanking region of the IL-8 gene, involving the transcription factors nuclear factor for interleukin-6 (NF-IL-6) and nuclear factor KB (NF-KB). The human melanoma cell line A3 was derived from G-361 cells by stable transfection with an IL-8 promoter-luciferase construct containing these sequences. la,2S-Dihydroxyvitamin D, (calcitriol) repressed IL-8 promoter activity induced by tumor necrosis factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
3
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 51 publications
3
51
3
2
Order By: Relevance
“…Vitamin D has shown a strong immunomodulatory capacity; high VDR levels have been reported in macrophages, dendritic cells, T lymphocytes, and B lymphocytes supports the conception of its fundamental role in combating bacteria, and preventing both autoimmune diseases and chronic inflammatory states (47)(48)(49)(50). The available evidence of extra-skeletal vitamin D actions and related health benefits is growing (5,7,9,.…”
Section: Vitamin D: a Classic Perspective In Briefmentioning
confidence: 85%
“…Vitamin D has shown a strong immunomodulatory capacity; high VDR levels have been reported in macrophages, dendritic cells, T lymphocytes, and B lymphocytes supports the conception of its fundamental role in combating bacteria, and preventing both autoimmune diseases and chronic inflammatory states (47)(48)(49)(50). The available evidence of extra-skeletal vitamin D actions and related health benefits is growing (5,7,9,.…”
Section: Vitamin D: a Classic Perspective In Briefmentioning
confidence: 85%
“…Moreover, it was found that topical administration of calcitriol can strongly reduce corneal neovascularization inhibiting leucocyte migration, and could also inhibit IL-1 alpha, IL-1 beta and IL-8 production by human corneal cells in vitro [31]. This could be partly because of its capacity to downregulate nuclear factor-kappa B [32]. Recently, one report Control group (n = 99) (Proliferative, n = 73 ; preproliferative DR, n = 28) (Absent, n = 32 ; background DR, n = 67)…”
Section: Discussionmentioning
confidence: 99%
“…The displacement of AP-1 leads to the inhibition of gene expression. Both RXR/VDR heterodimers and VDR monomers have been demonstrated to be involved in the inhibition (Alroy et al, 1995;Harant et al, 1997;Takeuchi et al, 2002).…”
Section: B Vitamin D Receptor Functionmentioning
confidence: 99%